2017
DOI: 10.1016/j.chembiol.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

A Small-Molecule Inhibitor of Bax and Bak Oligomerization Prevents Genotoxic Cell Death and Promotes Neuroprotection

Abstract: Aberrant apoptosis can lead to acute or chronic degenerative diseases. Mitochondrial outer membrane permeabilization (MOMP) triggered by the oligomerization of the Bcl-2 family proteins Bax/Bak is an irreversible step leading to execution of apoptosis. Here, we describe the discovery of small-molecule inhibitors of Bax/Bak oligomerization that prevent MOMP. We demonstrate that these molecules disrupt multiple, but not all, interactions between Bax dimer interfaces thereby interfering with the formation of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
88
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(88 citation statements)
references
References 60 publications
(110 reference statements)
0
88
0
Order By: Relevance
“…Small molecule inhibitors targeting Bax 44 exert a neuroprotective effect. 45 Likewise, modulation of autophagy by small molecules such as rapamycin results in a neuroprotective effect in several neurodegenerative diseases, including Parkinson’s disease, where rapamaycin enhances clearance of the pathological protein α -synuclein. 46 Rapamycin functions to induce autophagy by binding FK506 binding protein 12 and then inhibiting phosphorylation of mTOR.…”
Section: Resultsmentioning
confidence: 99%
“…Small molecule inhibitors targeting Bax 44 exert a neuroprotective effect. 45 Likewise, modulation of autophagy by small molecules such as rapamycin results in a neuroprotective effect in several neurodegenerative diseases, including Parkinson’s disease, where rapamaycin enhances clearance of the pathological protein α -synuclein. 46 Rapamycin functions to induce autophagy by binding FK506 binding protein 12 and then inhibiting phosphorylation of mTOR.…”
Section: Resultsmentioning
confidence: 99%
“…Also, because understanding how BH3-only proteins engage their pro-survival relatives has guided the development of the exciting new class of ''BH3 mimetic'' anti-cancer drugs (Adams and Cory, 2018), clarifying how BH3-only proteins trigger BAX should advance the search for drugs that either directly promote its activation (for cancer) or inhibit it in pathologies with excessive apoptosis (e.g., for stroke or degenerative disorders). Intriguingly, there may well be a therapeutic window for such compounds targeting BAX (Niu et al, 2017;Reyna et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the permeabilizing unit consists of the symmetric dimer form of Bax, as suggested by previous reports (Subburaj et al, 2015, Westphal et al, 2014. In support of this idea, one recent study (Niu et al, 2017) identified small-molecule inhibitors of Bax-mediated membrane permeabilization that caused the formation of incorrect dimers that could not progress to higher-order oligomers. The authors interpreted the results to mean that monomers are insufficient to form pores.…”
Section: Bax Higher-order Oligomers Are Not Required For Apoptotic Pomentioning
confidence: 75%